2008
DOI: 10.17796/jcpd.33.2.82r1tp71x75m5345
|View full text |Cite
|
Sign up to set email alerts
|

In vivo outcomes of Indirect Pulp Treatment using a Self-etching Primer versus Calcium Hydroxide over the Demineralized Dentin in Primary Molars

Abstract: Objective: To evaluate the clinical and radiographic outcomes (24 months) of indirect pulp treatment (IPT)in primary teeth when a self-etching primer or a calcium hydroxide layer was used over the remaining carious dentin. Study design: Primary molar teeth with deep carious lesions without signs and symptoms of irreversible pulpitis were divided into two groups, according to the capping material: Experimental group(1): self-etching adhesive system (Clearfill SE Bond); and Control group (2): calcium hydroxide l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…) and four compared it with self‐etch adhesives (Büyükgüral & Cehreli , Casagrande et al . , , Dalpian et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…) and four compared it with self‐etch adhesives (Büyükgüral & Cehreli , Casagrande et al . , , Dalpian et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…CH was compared with an inert material (wax or gutta-percha) in four studies (Pinto et al 2006, Franzon et al 2007, Bressani et al 2013. Seven studies compared CH with adhesive systems, of which four studies compared CH with total-etch materials (Falster et al 2002, B€ uy€ ukg€ ural & Cehreli 2008, Casagrande et al 2009, Dalpian et al 2014) and four compared it with self-etch adhesives (B€ uy€ ukg€ ural & Cehreli 2008, Casagrande et al 2008, Dalpian et al 2012. In the majority of included studies, a resin composite was used as the restorative material.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…14,15 PCR has demonstrated effectiveness in terms of microbiological, histological, biochemical and clinical-radiographic outcomes. [3][4][5][6]16,17 Although the majority of the researches consider the maintenance of pulp tissue vitality in acute deep carious lesions as the main outcome, the performance of the restorations over the carious dentin is not well documented. Ribeiro et al have shown by scanning electron microscopy the presence of an altered hybrid zone formed over the carious dentin, but limited information is available about the repercussion of this interaction over the time.…”
Section: Introductionmentioning
confidence: 99%
“…[162129] This article provided evidence that dentin reorganization and mineral changes were not dependent on the material placed in contact with the carious tissue, suggesting that the carious arrestment is a host-driven process rather than a material-induced process. [30]…”
Section: Discussionmentioning
confidence: 99%